PROCESSING PRODUCTS USING CATFISH AS RAW MATERIAL TO ENHANCE THE VALUE OF CATFISH IN THE SARIWANGI VILLAGE - Taufik, Yusman; Rukmana, Jaka; Rahayu, Gita; Luwandi, Revo; Al-Githrif, Muhammad Syamaidzar (LPPM Univ. Ibn Khaldun Bogor, 2023)
The activity aims to provide training related to the production of processed food using catfish meat as the main ingredient. Catfish meat has a fine texture and a slightly pale color, allowing it to be categorized as white meat, similar to chicken. Its high protein content and unsaturated fatty acids make catfish meat beneficial for maintaining tissue health, cellular formation, and brain intelligence. Catfish meat is highly recommended for consumption by children in the growth phase, especially toddlers. With its high protein content, low cholesterol level, tender muscle fibers, and more affluent organoleptic properties, catfish meat is preferred by consumers. Efforts to utilize catfish meat have included training on diversifying food products made from catfish meat. Since 2021, the Sariwangi Village Government has collaborated with the Faculty of Engineering at Pasundan University, starting from developing nanobubble technology for catfish farming and focusing more on training for processing products using catfish meat by the year 2023. The intended outcome of this activity is processed food products made from catfish meat that are ready for the market. The products developed are expected to serve as the foundation for a village-owned business unit.